2012
DOI: 10.1021/es302267a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Structure on the Relative Reactivity of Naphthenic Acids in the UV/H2O2 Advanced Oxidation Process

Abstract: The large volume of oil sands process-affected water (OSPW) produced by the oil sands industry in Northern Alberta, Canada, is an environmental concern. The toxicity of OSPW has been attributed to a complex mixture of naturally occurring acids, including naphthenic acids (NAs). Highly cyclic or branched NAs are highly biopersistent in tailings ponds, thus understanding structure-reactivity relationship for NAs is very important for OSPW reclamation. In this study, we hypothesized that large, branched and cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 45 publications
4
22
1
Order By: Relevance
“…The radicals then went on to abstract hydrogen from the NAs, instigating their oxidative degradation. Structure selective degradation, similar to the findings of Perez-Estrada et al [44] and Afzal et al [46], was also observed for this process. The authors reported an NA removal rate of 80 ± 2% at pH $ 8.3.…”
Section: Advanced Oxidationsupporting
confidence: 90%
See 4 more Smart Citations
“…The radicals then went on to abstract hydrogen from the NAs, instigating their oxidative degradation. Structure selective degradation, similar to the findings of Perez-Estrada et al [44] and Afzal et al [46], was also observed for this process. The authors reported an NA removal rate of 80 ± 2% at pH $ 8.3.…”
Section: Advanced Oxidationsupporting
confidence: 90%
“…The authors observed rapid degradation for both systems, with half-lives of 3.32 and 3.61 h for the commercial and native NAs, respectively. As reported in other works discussed here [44,46], selective degradation of higher molecular weight NAs was observed. Interestingly, the authors reported that in some cases the presence of TiO 2 did not result in significant half-life reduction of the NAs.…”
Section: Advanced Oxidationsupporting
confidence: 89%
See 3 more Smart Citations